Density evaluation of a coastcross-1 (Cynodon dactylon (L.) Pers) pasture under grazing in different levels of dry matter residue - Cecato, Ulysses (2008)
This experiment was carried out in Arenito Research Center-UEM, in Cidade Gaúcha-PR, from October/1997 to March /1998, to evaluate in coastcross-1 (Cynodon dactylon (L.) Pers) grazing, in four levels of dry matter residue (DMR: 1,978; 2,130; 2,545; 3,857 kg of DM/ha), with a continuous allotment system and variable number of allotments, the densities and participation of botanical component. A completely randomized design with two replications was used. Forage density, participation of botanical components and leaf/stem ratio were evaluated in inferior strata (0-10 cm) and superior ones (10-20 cm) of the pasture, according to the levels of DMR. The pasture density (g of DM/m3) in superior and inferior strata had a positive relation with the DMR levels and negative when associated to the period (days) of the experiment. Dead material (DM) percentage was higher in the inferior stratum than green stem (GC)and green leaves (GL) percentages. In the superior stratum, DM and GL had a greater participation, however the GL increased while DM levels increased as well.